A Novel Food Wastewater Treatment Approach: Developing a Sustainable Fungicide for Agricultural Use - Zikhona Tshemese; Laura Buzón-Durán; María Cruz García-González; Nirmala Deenadayalu; Beatriz Molinuevo-Salces (Fermentation)
Three wastewater sources, namely slaughterhouse wastewater, cheese whey, and wine lees, were used for volatile fatty acid (VFA) production with the aim of reducing polluted wastewater discharge to the water bodies and creating a useful product. Cheese whey and wine lees were proved to be good substrates to produce VFAs, obtaining maximum bioconversion percentages in g COD-VFA/g TCOD initial of 90% and 72% for cheese whey and wine lees, respectively. The composition of the VFAs produced from each wastewater stream varied, with acetic, propionic, isobutyric, and isovaleric acids being the most dominant. These VFAs were used as an environmentally friendly fungicide against Fusarium culmorum, resulting in a reduction of the radial mycelial growth of Fusarium culmorum for all the effluents tested. A thermal pretreatment of the VFAs resulted in an improved antifungal efficiency if compared to the untreated VFAs or a UV pretreatment.